SULTR3s function in chloroplast sulfate uptake and affect ABA biosynthesis and the stress response - Chen, Zhen; Hell, Rüdiger; Wirtz, Markus (Plant physiology, 2019)
Plants are major sulfur reducers in the global sulfur cycle. Sulfate, the major natural sulfur source in soil, is absorbed by plant roots and transported into plastids, where it is reduced and assimilated into Cys for further metabolic processes. Despite its importance, how sulfate is transported into plastids is poorly understood. We previously demonstrated using single Arabidopsis (Arabidopsis thaliana) genetic mutants that each member of the sulfate transporter (SULTR) subfamily 3 was able to transport sulfate across the chloroplast envelope membrane. To resolve the function of SULTR3s, we constructed a sultr3 quintuple mutant completely knocking out all five members of the subfamily. Here we report that all members of the SULTR3 subfamily show chloroplast membrane localization. Sulfate uptake by chloroplasts of the quintuple mutant is reduced by more than 50% compared with the wild type. Consequently, Cys and abscisic acid (ABA) content are reduced to ∼67 and ∼20% of the wild-type level, respectively, and strong positive correlations are found among sulfate, Cys, and ABA content. The sultr3 quintuple mutant shows obvious growth retardation with smaller rosettes and shorter roots. Seed germination of the sultr3 quintuple mutant is hypersensitive to exogenous ABA and salt stress, but is rescued by sulfide supplementation. Furthermore, sulfate-induced stomatal closure is abolished in the quintuple mutant, strongly suggesting that chloroplast sulfate is required for stomatal closure. Our genetic analyses unequivocally demonstrate that sulfate transporter subfamily 3 is responsible for more than half of the chloroplast sulfate uptake and influences downstream sulfate assimilation and ABA biosynthesis.
Nach Seite 604 ist im pdf eine weitere Seite mit "Correction" enthalten
Gesehen am 31.03.2020